2022
DOI: 10.1007/s11239-022-02642-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of poly-arginine peptides R18D and R18 on alteplase and tenecteplase thrombolysis in vitro, and neuroprotective stability to proteolysis

Abstract: The poly-arginine peptides R18D and R18 represent novel potential neuroprotective treatments for acute ischaemic stroke. Here we examined whether R18D and R18 had any significant effects on the thrombolytic activity of alteplase (tPA) and tenecteplase (TNK) on clots formed from whole blood in an in vitro thrombolysis plate assay. R18D and R18 were examined at concentrations of 0.25, 0.5, 1, 2, 4, 8 and 16 µM during the 1-h thrombolytic assay. We also included the well-characterised neuroprotective NA-1 peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…NA-1(a polypeptide, C 105 H 188 N 42 O 30 , molecular weight: 2518.88) and Y-3 (a chemical compound, C 24 H 27 Cl 2 NO 4 , molecular weight: 463.13) are two different types PSD95 inhibitors. Preclinical studies have demonstrated that administering NA1/Y-3 during the acute stage of stroke can minimize temporary and permanent damage 21-24 . After 24 hours of administration, the brain tissue was stained with TTC to label the area of brain infarction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NA-1(a polypeptide, C 105 H 188 N 42 O 30 , molecular weight: 2518.88) and Y-3 (a chemical compound, C 24 H 27 Cl 2 NO 4 , molecular weight: 463.13) are two different types PSD95 inhibitors. Preclinical studies have demonstrated that administering NA1/Y-3 during the acute stage of stroke can minimize temporary and permanent damage 21-24 . After 24 hours of administration, the brain tissue was stained with TTC to label the area of brain infarction.…”
Section: Resultsmentioning
confidence: 99%
“…Preclinical studies have demonstrated that administering NA1/Y-3 during the acute stage of stroke can minimize temporary and permanent damage [21][22][23][24] . After 24 hours of administration, the brain tissue was stained with TTC to label the area of brain infarction.…”
Section: Ico Injection Bypassed Bbb To Reach the Brain Parenchymamentioning
confidence: 99%
“…Compared with general heparin, dalteparin sodium injection is more effective in antithrombotic activity and in inhibiting coagulation factor Xa [12]. Its benefits are mainly due to its antithrombotic effect which results from the application of the fibrinolytic system or the function of vessel wall [13]. Hence, this study was aimed to further evaluate the efficacy of combining the above two drugs for the management of lower extremity deep venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Meloni et al are actively studying peptides of this class in vitro for the activity of the thrombolytic agents alteplase (tPA) and tenecteplase (TNK). In one of the latest studies by the Meloni team, it was shown that arginine-rich peptides R18D (polyarginine-18, D-isomer) and R18 (polyarginine-18, L-isomer) (Table 1), when co-administered with thrombolytic agents, increase the maximum activity of the thrombolysis reaction while maintaining these neuroprotective properties [58]. Thus, the polyarginine peptides R18D and R18 represent new potential neuroprotective agents for the treatment of acute IS, the administration of which can have a significant effect in clinical use during clot thrombolysis.…”
Section: Arginine-rich Peptidesmentioning
confidence: 99%